An analysis of Section 80A(C)(ii) of the Income Tax Act no. 58 of 1962 as amended - Geldenhuys, Bernard; Van Schalkwyk, Linda (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MAcc)--University of Stellenbosch, 2009.